Antibacterial And In Vitro Antioxidant Activities Of Some 4-amino-1,2,4-triazole-5(4h)-thione Derivatives - Manjula, P. S.; Sarojini, B. K.; Darshan Raj, C. G. (University of Eloued جامعة الوادي, 2015)
This work represents the synthesis and characterization some new versatile intermediates namely 4-amino-1,2,4-triazole-5(4H)-thione derivatives in a one-step fusion method. The method works to be superior compared to the existing method by Reed and Handel which consists of four steps. The antibacterial activity of compounds is tested against Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Staphilococcus aureus. The compounds exhibited species specific activity. Among the tested compounds, 1a and 1b exhibited good activity at moderately low concentration (31.25µg/mL) against tested strains of bacteria. DPPH (1,1-diphenyl-2-picryl-hydrazyl), FRAP (ferric reducing antioxidant power) and Lipid peroxidation assays are performed to determine the in vitro antioxidant activities. The compound 1e exhibited good antioxidant activity among the tested compounds.
Articale in Journal of fundamental and Applied Sciences Vol. 07, N. 03
Keywords: 1,2,4-triazole; Antibacterial; In vitro; Antioxidant; DPPH assay; FRAP assay; Lipid Peroxidation assay.